2011
DOI: 10.1097/brs.0b013e3181d952dc
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fibrinogen Plasma Concentration Is Associated With Perioperative Bleeding and Transfusion Requirements in Scoliosis Surgery

Abstract: The results indicate that preoperative fibrinogen concentration is a limiting factor for postoperative hemostasis during and after scoliosis surgery. Preoperative measurement of fibrinogen concentration provides more information about bleeding volume and transfusion requirements than standard screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…Our findings are congruent with the growing body of literature that emphasizes plasma fibrinogen level as a potential modifiable risk factor for perioperative hemorrhage161718192021. These studies indicate that lower fibrinogen, even within normal limits, are correlated with increased bleeding and that higher levels of fibrinogen are associated with better outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are congruent with the growing body of literature that emphasizes plasma fibrinogen level as a potential modifiable risk factor for perioperative hemorrhage161718192021. These studies indicate that lower fibrinogen, even within normal limits, are correlated with increased bleeding and that higher levels of fibrinogen are associated with better outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…During coagulation, thrombin cleaves fibrinogen, producing soluble fibrin monomers that are able to be cross-linked by factor VIIIa to form a network on which a clot is built; fibrinogen also plays a role in platelet aggregation15. Decreased plasma fibrinogen levels have been identified as a potential modifiable risk factor for perioperative bleeding in cardiothoracic and orthopedic surgeries16171819. Lower perioperative fibrinogen levels, even within the normal reference range, have been shown to be associated with an increased risk of postoperative bleeding complications in patients undergoing elective intracranial surgery2021.…”
mentioning
confidence: 99%
“…7 A prospective observational trial in adolescents who underwent major spine surgery demonstrated that preoperative fibrinogen concentrations predict mean total perioperative blood loss. 4 Thus, restoration of adequate fibrinogen concentrations plays a major role in maintenance of effective haemostasis. As in most European countries cryoprecipitate is not available, and fresh frozen plasma (FFP) has demonstrated questionable efficacy in restoring diminished fibrinogen concentrations after perioperative bleeding, [8][9][10] administration of purified fibrinogen concentrate has become the standard of care in a number of countries, including Switzerland.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…2 3 Both major paediatric orthopaedic surgery and craniosynostosis surgery are frequently associated with moderate to severe bleeding. [4][5][6] The development of hypofibrinogenaemia is a major reason for coagulopathic bleeding during craniosynostosis surgery. 7 A prospective observational trial in adolescents who underwent major spine surgery demonstrated that preoperative fibrinogen concentrations predict mean total perioperative blood loss.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…In contrast, Carling et al [6] more recently reported that total bleeding volume in adolescent idiopathic scoliosis patients correlated significantly with preoperative fibrinogen concentration, but neither with platelet count, aPTT, nor with PT. Although still within the ''normal'' range, bleeders had significantly lower preoperative fibrinogen plasma concentration than nonbleeders (2.660.6 vs. 3.160.6 g/L, p5.002) [6].…”
mentioning
confidence: 79%